Can correcting the market failures of credence goods promote corporate innovation? Evidence from compulsory food safety liability insurance - Wang, Yaodong; Wu, Maoguo (Frontiers in Sustainable Food Systems, 2025)
Employing a staggered difference-in-differences design, this study examines the impact of China's Compulsory Food Safety Liability Insurance (CFSLI) policy on corporate innovation within the food industry. Empirical results demonstrate that CFSLI implementation significantly stimulated innovation among affected firms. This positive effect was heterogeneous, exhibiting greater magnitude in non-state-owned enterprises and firms operating in regions with higher levels of marketization. The core findings withstand a comprehensive battery of robustness checks. Investigation into the underlying mechanisms reveals that the policy primarily fosters innovation by alleviating financing constraints, augmenting R&D investment, and enhancing corporate risk-bearing capacity. Beyond stimulating innovation, the CFSLI policy also significantly enhanced the total factor productivity and overall performance of food companies. These findings collectively indicate that the CFSLI policy not only facilitated the effective translation of innovation inputs into outputs but also supported broader corporate growth. This research contributes to the literature by providing novel empirical evidence on the innovation and productivity effects of mandatory liability insurance within the credence goods sector. It offers valuable insights for policymakers seeking to leverage institutional mechanisms, such as liability insurance, to promote innovation and development in analogous industries characterized by information asymmetry, including pharmaceuticals and medical services.